Proper hand washing practices in school canteen: a qualitative study on food handlers' belief - Ahmad, I. A.; Ungku Zainal Abidin, Ungku Fatimah; Mahyudin, Nor Ainy; Ab Rashid, N. K. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Improving hand washing practice among food handlers is one of the ways to reduce food borne illness. This study aimed to assess behavioural belief, normative and control beliefs underpinning food handlers’ decision to perform hand washing practices in school canteen in Malaysia. A qualitative study comprising eight focus group discussions with 71 food handlers were conducted to elicit the underlying belief specific to hand washing practices. Respondents from school canteen within Klang Valley were recruited using purposive sampling strategy. All focus group audio recordings were transcribed verbatim. A thematic content analysis was conducted using Atlas.ti software to code, manage and analyze data. Results obtained from the focus group discussions were coded according to key concepts in the Theory of Planned Behaviour (TPB) framework which explain behavioural belief (i.e. advantages and disadvantages of hand washing), normative belief (i.e. an individual’s perception of social normative pressure) and control belief (i.e. barriers and facilitators) to perform hand washing. Themes emerge for the advantages of proper hand washing are cleanliness, prevent bacteria/virus infection, reduce food poisoning risk, while the disadvantages are time pressure, hassle, and work load pressure. The barriers for proper hand washing identified were time pressure, work load pressure, the frequency of hand washing required, steps in proper hand washing, and availability of hand washing soap. The facilitators for hand washing practices include poster reminder, reminder from manager/owner and rewards/punishment from manager/owner. Themes found under normative belief are the influence from school administration, manager, co-worker and health inspector. In summary, all the beliefs elicited may provide valuable information for the development and evaluation of intervention strategies to improve food handlers’ proper hand washing practices.